Oscillometric blood pressure measurement: modeling and analysis of the area oscillogram and height oscillogram - Dhamotharan, Vishaal; Cheng, Hao-Min; Sung, Shih-Hsien; Chen, Chen-Huan; Landry, Cederick; Freithaler, Mark; Mahajan, Aman; Shroff, Sanjeev G.; Hahn, Jin-Oh; Mukkamala, Ramakrishna (Frontiers in Physiology, 2025)
ObjectiveOscillometry is the most popular blood pressure (BP) measurement method. Conventionally, BP is computed from the oscillation height versus cuff pressure function (“height oscillogram”). However, the oscillation shape also changes with cuff pressure. The objectives were to mathematically model oscillation shape and height variations as a function of cuff pressure and analyze these models using patient data.MethodsThe patient data comprised oscillometric arm cuff pressure and invasive brachial BP waveforms from 109 patients with diverse BPs. The data were analyzed to show that the oscillation area versus cuff pressure function (“area oscillogram”) in particular could be reliably constructed while offering distinct information to the height oscillogram. An analytical model of the area oscillogram was developed with four unknown parameters representing the widths of the brachial artery compliance curve over positive and negative transmural pressure ranges and systolic and diastolic BPs. With invasive systolic and diastolic BPs as inputs, this model and a previous height oscillogram model with the same four parameters, were evaluated in terms of fitting individual patient oscillograms. The impact of key assumptions of the models was evaluated as well.ResultsThe area and height oscillogram models fitted the patient data well with errors of 6.9% ± 0.3% and 8.7% ± 0.4%, respectively. Cuff-arm-artery viscoelasticity affected the height oscillogram model fitting, while cuff-arm system nonlinearity may affect area oscillogram model parameter estimates.ConclusionDespite simplifying assumptions, the proposed area and previous height oscillogram models can reproduce measured patient oscillograms well. These models may ultimately help improve oscillometric BP measurement accuracy.